2010
DOI: 10.4111/kju.2010.51.10.719
|View full text |Cite
|
Sign up to set email alerts
|

Use of NTrap® during Ureteroscopic Lithotripsy for Upper Ureteral Stones

Abstract: PurposeThis study aimed to determine the value of the NTrap® (Cook Urological INC, USA), which was designed to block the upward movement of stones during ureteroscopic lithotripsy.Materials and MethodsWe reviewed the data of 144 patients who underwent ureteroscopic lithotripsy for an upper ureteral stone from June 2006 to May 2010. Sixty-eight patients who underwent ureteroscopic lithotripsy without the use of the NTrap® were assigned to Group I and 76 patients who underwent ureteroscopic lithotripsy with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…The need to perform ESWL and ESWL with DJ was significantly higher in the control group (p <0.05). Several studies in the treatment of ureteroscopic lithotripsy have shown that the most common cause of failure of lithotripsy can be attributed to stone retropulsion and the movement of stone pieces into the pelvis or kidney calyx during lithotripsy [11]. This can increase costs due to secondary interventions and morbidity [12,[16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The need to perform ESWL and ESWL with DJ was significantly higher in the control group (p <0.05). Several studies in the treatment of ureteroscopic lithotripsy have shown that the most common cause of failure of lithotripsy can be attributed to stone retropulsion and the movement of stone pieces into the pelvis or kidney calyx during lithotripsy [11]. This can increase costs due to secondary interventions and morbidity [12,[16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of stone retropulsion or the escaping of the stone is affected by factors such as washing fluid pressure, the energy source type of transurethral lithotripsy, the location and the amount of stone compression in the ureter, and the proximal ureter dilatation severity. The rate of stone migration in pneumatic and electrohydraulic lithotripters is higher than that of a laser lithotripter [11]. Stone upward migration may increase the time of lithotripsy due to time waste of trapping stones fragments that have migrated to the back.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most significant results have been published in a recent meta-analysis [17] including 2 randomized controlled trials [18,19] and 1 case-control study [20]: stonefree rate for N-Trap™ ranged from 83 to 100 %, which was significantly higher than controls also at the pooled analysis [OR = 3.08, 95 % CI (1.45-6.53)].…”
Section: Discussionmentioning
confidence: 99%